Parallel CV-QRNG with Strict Entropy Evaluation - Zhicang Zheng; Xiaomin Guo; Fading Lin; Yingqi Wang; Yu Wang; Yanqiang Guo (Photonics, 2023)
Continuous-variable quantum random number generators (CV-QRNGs) have promising application prospects thanks to their advantages such as high detection bandwidth, robustness of system, and integratability. In major CV-QRNGs, the generation of random numbers is based on homodyne detection and discretization of the quadrature fluctuations of the EM fields. Any defectiveness in physical realization may leak information correlated with the generated numbers and the maximal amount of randomness that can be extracted in presence of such side-information is evaluated by the so-called quantum conditional min-entropy. The parallel CV-QRNG overcomes the rate bottleneck of the previous serial type scheme. As a type of device-trusted QRNG, its security needs to be better guaranteed based on self-testing or monitoring that can be rigorously enforced. In this work, four sideband modes of vacuum state within 1.6 GHz detection bandwidth were extracted parallelly as the entropy source, and 16-bit analog-to-digital conversion in each channel was realized. Without making any ideal assumptions, the transfer function of the homodyne and quantization system was measured based on beat method to calibrate the evaluation of the min-entropy. Based on the rigorous entropy evaluation with a hash security parameter of <semantics>εhash</semantics> = 2−110, a real-time generation rate of 7.25 Gbps was finally achieved.